Visual rehabilitation with scleral contact lenses in patients with irregular astigmatism - Cano-Blaires , Maria Alessandra; Vera Duarte, Guillermo Raúl; Blaires , Myriam Blaires (Medicina Clínica y Social, 2024)
Introduction: Scleral contact lenses (SCLs) are gas-permeable and are placed entirely on the sclera without contacting structures such as the cornea or limbus. These ECLs are designed to rehabilitate reduced vision of eyes with irregular corneas. Irregular astigmatism caused by corneal pathologies such as keratoconus, post-transplant, post-refractive surgery, or corneal degeneration produces poor visual acuity that cannot be corrected with air lenses, and the appearance of scleral contact lenses could be a therapeutic option in the treatment and optical correction of corneal pathologies. To determine the degree of improvement in visual acuity with adaptation of scleral lenses. Methodology: This was an observational, descriptive, retrospective, cross-sectional, retrospective study. Results: Forty cases of irregular astigmatism with different initial visual acuity effects were observed prior to the fitting of Scleral Lenses. The mean visual acuity (VA) prior to correction with scleral lenses observed in the 40 cases was 20/200 with correction on the Snellen scale with a minimum (worst VA) equal to "finger-count vision" (represented as cases with 20/ 400 vision for quantification purposes) and a maximum (best VA) of 20/70. Nineteen cases (47.5%) restored their VA to normal values (20/20), and 30 cases (75%) improved their VA by at least 10-fold from the baseline. Discussion: In this study, a remarkable and constant improvement in visual acuity was observed in all the patients. Some patients experienced an increase of up to 20 times their initial visual acuity, achieving, in many cases, a visual acuity of 20/20 on the Snellen scale. These results indicate a promising treatment strategy with fewer adverse effects.